Risk factors for death including initial admission to COVID-19 quarantine before isolation vs. direct admission to isolation at King Edward VIII hospital in South Africa: A case-control study: 10.55131/jphd/2025/230320 - Manimani, Riziki Ghislain; Muzumbukilwa, Tambwe Willy; Esther, Furaha Bashengezi; Chiya, Wilbroda Hlolisile; Muthambi, Binjamin; Magula, Nombulelo (Journal of Public Health and Development, 2025)
Worldwide, the emergence of the novel coronavirus disease 2019 (COVID-19) has resulted in millions of deaths. This study aims to investigate the relationship between death during admission and various risk factors thereof including admission to COVID-19 quarantine before isolation vs. direct admission to isolation, among COVID-19 patients at King Edward VIII Hospital. A case-control study design was employed, involving 400 COVID-19 patients (200 cases and 200 controls by a 1:1 ratio). Patient information was retrospectively abstracted from medical records. Associations between risk factors and mortality were assessed using chi-square tests, followed by univariate and multivariate logistic regression analyses. Among the 200 cases, 133 were referred from primary or secondary levels of care, compared to 71 out of 200 controls. The mean age of patients was 55.6 years (SD: 16.2 years), and 177 (44.2%) patients were male. Out of the total number of patients, 181 (45.2%) patients were initially admitted to the COVID-19 quarantine ward before isolation, while 219 (54.7%) patients were directly admitted to the COVID-19 isolation ward. Increasing age (adjusted odds ratio [aOR]:˃ 60 years: 6.49 [95%CI: 2.97-14.16]), admission directly to isolation ([aOR]: 2.49[95%CI:1.53-4.06]), Fever ([aOR]: 1.74[95%CI:1.03-2.91]) Shortness of breath ([aOR]: 4.86[95%CI:2.53-9.35]), CKD (Chronic Kidney Disease) ([aOR]: 10.39 [95%CI:2.09-51.61]), and obesity ([aOR]: 4.85[95%CI:1.88-12.46]) were associated with death among COVID-19 patients during admission on multivariate analysis. Understanding and addressing these factors can help healthcare systems develop targeted strategies to improve patient outcomes and reduce mortality rates.